Design and Characteristics of a Single-Story Building Model Incorporating Waste - Mohamed Darwish; Mohamed Elnakeb; Marina Moawad; Marwan Mohamed Shawki; Ehab Abdelhamid; Donia Eldwib; Mohamed Nagib Abouzeid; Maram Saudy; Safwan Khedr; Khaled Nassar (Buildings)
The construction field is one of the largest sectors and industries worldwide. This industry is the main industry accused of contributing to greenhouse gases and increasing the effects of climate change. However, the construction industry is indispensable, accordingly in an attempt to decrease the greenhouse gas effects of construction this research presents the manuscript for building a one-story building with all components including waste products. The building model used a strip foundation with a concrete mix design incorporating recycled concrete as a partial replacement for aggregates, cement hollow blocks containing granite waste instead of conventional cement blocks, and sandwiched insulated panels made of wood-plastic composites for the roof. The structural soundness of the system was tested by loading it with a load surpassing its design load in addition to measuring the deflection and checking its abidance to the code limitations. The thermal efficiency was tested by measuring the temperatures in comparison with the outside of the building for a span of 7 days with data recorded every 1 h. Analysis of both the short-term and long-term costs and carbon emissions was performed by acquiring the carbon emissions per unit of material from literature and multiplying it by the quantities of the materials used within the different building alternatives. That study showed that the roofs made of Structural Insulated Panels (SIPs) using Wood-Plastic Composite (WPC) facings when used with hollow-block cement block walls have shown enduring cost efficiency and improved thermal insulation, leading to diminished energy usage, life-cycle expenses, and carbon emissions. Furthermore, the proposed system is more environmentally friendly than conventional reinforced concrete technologies due to their lower costs and emissions in addition to improving sustainability through utilizing recycled materials.